A pre-feasibility study to implement solar hot water (SHW) system to reduce the CO2 emissions - Akbar, Muhammad Ali; Rashid, Mahbubur; Embong, Abd Halim; Haja Mohideen, Ahmad Jazlan; Muhamamd, Munir Azam; Nazeer, Muhammad Uzair (IEEE org, 2020)
The world Green House Authorities are encouraging the industrial sector to use green energies since last two decades to reduce the CO 2 Emissions. Hot water and steam are one of the significant requirements in the industries, and to fulfill this requirement, natural gas boilers are commonly used by the industries. However, due to the vast usage of conventional boilers, the emission of CO 2 increases in the environment. Therefore, Solar Thermal Collectors (STC) gain the importance over natural gas boilers as green energy products in the industry to generate hot water and steam. The performance of STC depends on the different factors such as solar irradiation, non-shading area, cost, and heating capacity. The objective of this pre-feasibility study is to see the technical viability of the Solar Hot Water (SHW) system in order to fulfill the industrial hot water requirement. It can be observed from the result that SHW system is capable of generating averagely 614.75kW/day which can save 123.93 KG of CO 2 . Furthermore, the performance of the different type of solar collectors is also analyzed comprehensively. It is observed that the evacuated tube collector performs better as compared to the flat plate collector.